KADAR AIR DAN TOTAL MIKROBA PADA DAGING SAPI DI TEMPAT PEMOTONGAN HEWAN (TPH) BANDAR LAMPUNG - Deni Hernando; Dian Septinova; Kusuma Adhianto (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The aim of this research was: 1) to determine the water content of the meat in Bandar Lapung abattoirs; 2) to determine the microbial quality of the meat in Bandar Lampung abattoirs. The research was conducted at March 2014 continously from Bandar Lampung abattoirs. The analysis of the water content was conducted in Laboratorium Nutrisi Ternak, Jurusan Peternakan while the analysis of the microbial quality conducted in Laboratorium Penguji Balai Veteriner Lampung. The method of research was survey. The obtain data was analyzed by using the descriptive quantitative analysis.The analysis shows that water content of the meat in Mrs. Mul’s abattoir were 71,92% and 71,55%. The total microbial count were 0,67 x105 CFU/g and 1,2 x105 CFU/g. The water content of the meat in H. Bustomi’s abattoir were 74,84% and 74,43%. The total microbial count were 0,46x105 CFU/g and 5,9 x105 CFU/g. The water content of the meat in H. Udin’s abattoir were 74,24% and 73,14%. The total microbial count were 4,9x 105 CFU/g and 0,088x105 CFU/g. The water content of the meat in Mr. Ampan’s abattoir were 72,22% dan 72,65%. The total microbial count were 4,4x105 CFU/g and 0,075x105 CFU/g. Based on the result, it was concluded that the meat from Bandar Lampung abattoirs were still proper for consumption.